A consistent collinear triad approximation for operational wave models. (August 2016) - Salmon, J.E.; Smit, P.B.; Janssen, T.T.; Holthuijsen, L.H.
Highlights: Original collinear approximation (OCA) is overly sensitive to directional aperture. The OCA becomes unbounded in the limit of unidirectional waves. Modified collinear approximation is proposed to remove the internal inconsistency. Consistent Collinear Approximation is applicable to wider range of wave conditions. Numerical simulations show changes proposed improve robustness and performance. Abstract: In shallow water, the spectral evolution associated with energy transfers due to three-wave (or triad) interactions is important for the prediction of nearshore wave propagation and wave-driven dynamics. The numerical evaluation of these nonlinear interactions involves the evaluation of a weighted convolution integral in both frequency and directional space for each frequency-direction component in the wave field. For reasons of efficiency, operational wave models often rely on a so-called collinear approximation that assumes that energy is only exchanged between wave components travelling in the same direction (collinear propagation) to eliminate the directional convolution. In this work, we show that the collinear approximation as presently implemented in operational models is inconsistent. This causes energy transfers to become unbounded in the limit of unidirectional waves (narrow aperture), and results in the underestimation of energy transfers in short-crested wave conditions. We propose a modification to the collinear approximation to remove this inconsistency and to make it physically more realistic. Through comparison with laboratory observations and results from Monte Carlo simulations, we demonstrate that the proposed modified collinear model is consistent, remains bounded, smoothly converges to the unidirectional limit, and is numerically more robust. Our results show that the modifications proposed here result in a consistent collinear approximation, which remains bounded and can provide an efficient approximation to model nonlinear triad effects in operational wave models.